R&D and CEO departure date: do financial incentives make CEOs more opportunistic?. (27th March 2017) - Driver, Ciaran; Guedes, Maria João Coelho
Abstract: The purpose of this article is to examine whether Research and Development (R&D) expenditure is biased downward because of self-serving behavior of highly incentivized managers. This offers an insight into the general relationship between incentives and opportunism. Using instrumental variables and panel-data methods for a sample of high R&D spenders in the UK, we examine whether R&D is reduced in cases of imminent departure of the CEO. Results show evidence for this but only for the sample above the median in intensity of stock and options in the compensation package. This suggests that opportunism is enhanced by inappropriately strong incentives. The main results are robust to the inclusion of a number of corporate governance variables.